1999
DOI: 10.1590/s1415-47571999000300007
|View full text |Cite
|
Sign up to set email alerts
|

Intrapopulational genetic differentiation in Anopheles (N.) darlingi Root, 1926 (Diptera: Culicidae) in the amazon region

Abstract: Four natural Amazonian Anopheles darlingi populations were analyzed for 19 loci, 12 of which showed variation, i.e., 68.4% of polymorphic loci. The Ariquemes, Rondônia, population was the most variable, with a large number of alleles per locus (2.26 ± 0.27) and high polymorphism (P = 63.15). The highest values of observed and expected intralocus heterozygosity were observed in the Manaus, Amazonas, population (Ho = 0.432 ± 0.11; He = 0.375 ± 0.08), and the lowest in the Cachoeira Porteira, Pará, population (Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…darlingi phylogenetic network represents various feasible topologies (areas full of boxes), indicating the relationships among specimens from different sites from Central and South America, the result suggests that a more intense sampling should be conducted to gain a clearer picture of the general population structure and evolutionary history of this species through its distribution range. 63 Haplotype M found by Mirabello and Conn 19 in Nechi, a locality in Antioquia, was identical to haplotype B found widely dispersed in the present work ( Figures 3 and 5 15,67 have shown that An. darlingi populations were highly homogeneous, and there were no clear correlations among genetic and geographic distance.…”
supporting
confidence: 82%
“…darlingi phylogenetic network represents various feasible topologies (areas full of boxes), indicating the relationships among specimens from different sites from Central and South America, the result suggests that a more intense sampling should be conducted to gain a clearer picture of the general population structure and evolutionary history of this species through its distribution range. 63 Haplotype M found by Mirabello and Conn 19 in Nechi, a locality in Antioquia, was identical to haplotype B found widely dispersed in the present work ( Figures 3 and 5 15,67 have shown that An. darlingi populations were highly homogeneous, and there were no clear correlations among genetic and geographic distance.…”
supporting
confidence: 82%
“…darlingi was controversial (WHO 1984(WHO , 1988 due to small morphological variation (e.g. in the scales of hind 3-5 tarsomeres in specimens of the Belize populations, Harbach et al 1993), little interpopulational variation has been found based on morphological, isoenzymatic and DNA analyses pointing for the existence of a single species (Linthicum 1988, Freitas-Sibajev et al 1995, Manguin et al 1999, Santos et al 1999.…”
mentioning
confidence: 99%
“…González et al (2007) found average values of 0.374 and 0.309 with RAPD and Genetic differences in Anopheles darlingi AFLP markers, respectively. Santos et al (1999) found values ranging from 0.290 to 0.375 for populations of different states of Brazil. However, these values are low when compared with results obtained with codominant DNA markers such as microsatellites , and high when compared with values obtained with isozyme markers by Manguin et al (1999).…”
Section: Discussionmentioning
confidence: 98%
“…There was evidence of small population differences, evaluated by F st , genetic distance and analysis of molecular variance. Comparison between peri-and extra-domicile samples showed greater values of INTRODUCTION ability and structure in populations of A. darlingi in Central and South America (Rosa-Freitas et al, 1992;Mendes-dos-Santos et al, 1999;Manguin et al, 1999;Malafronte et al, 1999;Santos et al, 1999;Conn et al, 2006;Scarpassa and Conn, 2007;Mirabello et al, 2008). In general, the studies revealed medium to high levels of genetic variability and low or moderate population structure.…”
mentioning
confidence: 99%